“Everyday Resistance”: Women and Sexual Violence in Women Talking Film - Suci (Universitas Negeri Surabaya, 2025)
The research analyses the women's resistance to sexual violence in religious communities. This research aims to understand how the portrayed sexual violence against women and how women resist to sexual violence in religious communities. The research method applied is the descriptive qualitative method. Resistance theory by James Scott, including Covert resistance and Public resistance also applied in this research. The results show that women in religious communities resist sexual violence, such as rape, that they have experienced for generations committed by men in the community. The resistance carried out is in the form of covert resistance and public resistance. Covert resistance is carried out by discussing in a closed room without any of the authorities knowing, the resistance is in the form of a hidden transcript so that it does not create any changes. Furthermore, public resistance is carried out openly and has an impact on both life and future changes. This research highlights women’s resistance against sexual violence and the importance of understanding of sexual violence against women’s in a male-dominated as portrayed in Women Talking.